Strategies for Controlling Diabetes Mellitus in Adolescents through a Family Approach at Puskesmas after the COVID-19 Pandemic - Sira, Amaze Grace; Priskila, Loury; Wicaksono, Hendi; Simanjuntak, Mario Hendrian; Nappoe, Angela Aletha Biatrix; Julianto, Dayceline Helena (International Journal of Cell and Biomedical Science, 2024)
Background Non-communicable diseases (NCDs) have become a burden on the health system in Indonesia in recent years. The increasing prevalence of diseases such as heart disease, diabetes mellitus, and cancer has an impact on national health financing, and people's quality of life. This study is a literature review that aims to evaluate the relationship between NCD risk factors, the impact of the COVID-19 pandemic on early detection of chronic diseases, and the role of primary health facilities and family approaches in controlling NCDs. Methods Secondary data were obtained from various scientific journals and official reports through systematic searches in Clinical Key, Google Scholar, and PubMed. Discussion The review showed that risk factors such as body mass index (BMI), unhealthy diet, low physical activity, and family history significantly contributed to the increase in NCD cases. The COVID-19 pandemic has also caused serious disruptions to preventive health services, including decreased access to early detection of Type 2 Diabetes Mellitus Programs such as Posbindu PTM and PIS-PK conducted by Puskesmas have an important role in promotive and preventive efforts, although they are still faced with various obstacles. The family approach in implementing healthy living behaviors and early detection has proven crucial in supporting the success of NCD control. Conclusion: The integration of the family approach in the national NCD control strategy needs to be strengthened to improve the effectiveness of interventions and the quality of life of the community.